Seamless Learning to Enhancing Resilience and Professional Ethics in Higher Education Students - Widiyati , Theresia Dwi Siwi Candra; Setyosari , Punaji; Praherdhiono , Henry; Nakaya , Ayami; Khotimah, Khusnul (Journal of Ecohumanism, 2025)
This research explores the impact of seamless learning on resilience and professional ethics among polytechnic students by integrating the Transdisciplinary Learning Approach with the Aptitude Treatment Interaction (ATI) Model. The study employs a quasi-experimental design with a sample of 100 students, utilizing SMART Poltekad. This seamless learning platform facilitates experiences through its interactive features. Seamless learning, characterized by continuous, cross-context learning experiences, supports a cohesive and adaptive learning environment that fosters holistic student development. Using Two-Way MANOVA analysis, findings reveal significant improvements in academic achievement (ρ = 0.000, ρ < 0.05), resilience (ρ = 0.000, ρ < 0.05), and professional ethics (ρ = 0.000, ρ < 0.05) in students exposed to the ATI and Transdisciplinary models compared to a control group. Learning motivation, however, did not demonstrate a statistically significant difference (ρ = 0.052, ρ > 0.05), suggesting context-dependent factors may influence motivation within the seamless learning framework. These findings underscore the potential of seamless learning, particularly when paired with seamless learning tools, to enhance resilience and professional ethics in polytechnic education. Future research could further explore the applicability of seamless learning models in diverse educational settings and examine long-term impacts on students’ professional and ethical development.